Alcaligenes faecalis Juj3 alleviates Plasmodiophora brassicae stress to cabbage via promoting growth and inducing resistance - Jia, Ruimin; Chen, Jing; Hu, Lifang; Liu, Xiaoran; Xiao, Keyu; Wang, Yang (Frontiers in Sustainable Food Systems, 2022)
Clubroot is a devastating disease threatening global cruciferous vegetable production caused by Plasmodiophora brassicae (Pb). We have evaluated the positive effects of the Alcaligenes faecalis Juj3 on cabbage growth promotion and Pb stress alleviation through pot and field experiments. The Juj3 strain was isolated from a healthy cabbage rhizosphere with growth-promoting characteristics and was identified as A. faecalis based on morphological traits and phylogeny. Seed germination assays revealed that Juj3 inoculation enhances cabbage bud shoot and root growth. In pot experiments, inoculation with Juj3 fermentation powder at cabbage sowing dates significantly improved the seedling biomass. Combining seed treatments with root irrigation after transplanting considerably reduced the clubroot disease index and resulted in appreciable biocontrol efficacy (83.7%). Gene expression analyses of cabbage after Juj3 inoculation showed that PR2 and EIN3 expression were significantly up-regulated. Physiologically, Juj3 inoculation enhanced cabbage chlorophyll content and root activity in a normal environment. Irrespective of whether plants were under normal environment or Pb stresses, Juj3 improved photosynthesis. Field trial analyses revealed that Juj3 exhibits satisfactory biocontrol efficacy in cabbage (51.4%) and Chinese cabbage (37.7%). Moreover, Juj3 could also enhance cabbage and Chinese cabbage biomass to improve the yield quality. These findings pave the way for future use of A. faecalis as biocontrol agents for clubroot and reveal the great potential of the rhizobacterium for plant growth-promoting applications in agriculture and horticulture.